Identification and nucleotide sequence of genes involved in the synthesis of lactocin 705, a two-peptide bacteriocin from Lactobacillus casei CRL 705 - Cuozzo, Sergio Antonio (2000)
The structural gene determinants of lactocin 705, a bacteriocin produced by Lactobacillus casei CRL 705, have been amplified from a plasmid of approximately 35 kb and sequenced. Lactocin 705 is a class IIb bacteriocin, whose activity depends upon the complementation of two peptides (705α and 705β) of 33 amino acid residues each. These peptides are synthesized as precursors with signal sequences of the double-glycine type, which exhibited high identities with the leader peptides of plantaricin S and J from Lactobacillus plantarum, brochocin C from Brochotrix campestris, sakacin P from Lactobacillus sake, and the competence stimulating peptides from Streptococcus gordonii and Streptococcus mitis. However, the two mature bacteriocins 705α and 705β do not show significant similarity to other sequences in the databases.